The relationship of the colombian state and the paramilitary phenomena: for historical enlightening (2005)
The process that is actually being developed by the government of President Alvaro Uribe and the AUC (name in Spanish for United Auto-defense of Colombia) still rises more questions than answers. This article poses a central question: Are they trying to overcome paramilitarism as a historical and structural phenomena or is it only a demobilizing and reinsertion program for the AUC, one of its specific military expressions? It is with the intention to throw some light on this thorny subject that the text presents three main themes: in the first one a brief historical round is made of the state policies in regards with paramilitarism, just as well as on the treatment that paramilitary groups have been subject to during the different stages of the peace process; in the second, an analysis of the policies and approach of this administration regarding paramilitarism is made and in the third a proposal is submitted for the creation of a historical enlightening commission about the state’s responsibility in the paramilitary phenomena as a main element to overcome it.